An Overview of Genomic Biomarker Use in Cardiovascular Disease Clinical Trials. Issue 4 (20th June 2019) - Adeniyi, Oluseyi; Ramamoorthy, Anuradha; Schuck, Robert; Sun, Jielin; Wilson, Jennifer; Zineh, Issam; Pacanowski, Michael
Abstract : Clinical trial designs targeting patient subgroups with certain genetic characteristics may enhance the efficiency of developing drugs for cardiovascular disease (CVD). To evaluate the extent to which genetic knowledge translates to the CVD pipeline, we analyzed how genomic biomarkers are utilized in trials. Phase II and III trial protocols for investigational new drugs for CVD and risk factors were evaluated for prospective and exploratory genomic biomarker use; drug targets were evaluated for the presence of evidence that genetic variations can impact CVD risk or drug response. We identified 134 programs (73 unique drug targets) and 147 clinical trials. Less than 1% ( n  = 1/147) trials used a genomic biomarker prospectively for in‐trial enrichment despite 32% ( n  = 23/73) of the drug targets having evidence of genetic variations. Additionally, 46% ( n  = 68/147) of the trials specified exploratory biomarker use. The results highlight an opportunity for more targeted CVD drug development by leveraging genomic biomarker knowledge.